Kompetensi Komunikasi Pegiat Penyandang Disabilitas dalam Menyuarakan Aspirasi Kelompok ke Pemangku Kepentingan (Kasus pada Perkumpulan Penyandang Disabilitas Indonesia Kota Semarang) - Octaviani, Averina; Rahardjo, Turnomo; Suryanto Gono, Joyo Nur (Interaksi Online, 2024)
This research aims to describe communication competence, find out the basis for developing communication competence as well as the formation of self-concept and self-development carried out by activists with disabilities PPDI Semarang City in voicing their aspirations. This research used descriptive qualitative methods and interpretive paradigms, observational data collection techniques and in-depth interviews with 4 informants consisting of 3 activists with disabilities PPDI Semarang City and 1 stakeholder from the Central Java Province Manpower Office. Theories used in this research are communication competence theory, attribution theory, and symbolic interaction and self-development theory. Results of this research show that activists with disabilities PPDI Semarang City have high communication competence with the fulfillment of three indicators of good communication competence, namely motivation in the form of feeling the same fate and responsibility as part of people with disabilities, the desire to escape negative stigma and bad labelling, and the desire to gain fulfillment of rights as persons with disabilities, knowledge in the form of content knowledge by all informants, however only two out of three informants have procedural knowledge, and the third is capable and without obstacles in line with the standards of relevant stakeholders, has active involvement, enthusiasm, enthusiasm , and high curiosity and provide constructive suggestions and input. Another result obtained is the basis for building communication competence because motivation is driven by awareness of gaps and the desire to seek change. The final results of selfconcept influence the formation of communication competence and voicing the aspirations of their group.